Value negotiation : how to finally get the win-win right - Falcão, Horacio (Prentice Hall/Pearson Education South Asia, 2010)
Value Negotiation: How to Finally Get the Win-Win Right examines the complicated world of negotiation and provides a simple and practical approach in helping negotiators learn how to consistently deliver the highest possible value at the lowest possible risk in the widest range of situations. The textbook consists of three parts: in Become a Negotiator, challenge yourself to rethink your foundations and assumptions about negotiation, in Prepare for Negotiation, find out how to choose a negotiation goal and strategy, and anticipate critical moments during negotiation and in Negotiate!, uncover how you can connect with negotiating parties, work towards gaining mutual value, and finally, make the best possible decision. In each part, a wide variety of dialogues, scenarios, discussion questions and exercises have been specially designed to prepare you for commonly experienced situations and settings in negotiation. For university professors, adopting the Value Negotiation book entitles you to request a comprehensive Instructor's Package that includes an Instructor's Manual and a set of teaching slides.